New records of two goby species from Taiwan, northwestern Pacific Ocean (Gobiiformes: Gobiidae) - Su, Yo; Hsu, Yu-Chieh; Ho, Hsuan-Ching (Zootaxa, 2025)
Two goby species, Egglestonichthys melanoptera (Visweswara Rao, 1971) and Obliquogobius yamadai Shibukawa & Aonuma, 2007, are recorded for the first time from southwestern Taiwan based on specimens collected by bottom trawl. The former is represented by four specimens, representing its northernmost distributed range. The latter is represented by a single specimen, marking the first record of the genus and species from Taiwan. This finding fills the distribution gap between Japan and the region spanning southern Indonesia to northwestern Australia. Detailed descriptions and photographs are presented, with comparisons to previously documented specimens and notes on morphological variation.